1981
DOI: 10.1056/nejm198104163041604
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriuria and Survival in Old Age

Abstract: We studied the effect of asymptomatic bacteriuria on survival in 342 healthy residents of a home for the aged. At entry into the study 76 subjects (22 per cent) had bacteriuria on two consecutive urine cultures. There were no differences in age distribution, blood pressure, hematocrit, smoking habits, cholesterol, or myocardial changes between bacteriuric and nonbacteriuric subjects. Median survival was 53 and 75 months in nonbacteriuric men and women 70 to 79 years old, and 45 months in all nonbacteriuric sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
3
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(57 citation statements)
references
References 20 publications
1
52
3
1
Order By: Relevance
“…Serum creatinine values in patients with significant bacteriuria did not differ from those of the rest of the patients. This 'abnormality' con firms our opinion that we must consider the increased positive urinary 'abnormalities' in the very old either as a normal phenomenon connected with ageing [1,10] or as a reflec tion of other disease processes present [4,8]. Significant bacteriuria should be treated with drugs only when the aged patient has symp toms of UTI.…”
Section: Discussionmentioning
confidence: 99%
“…Serum creatinine values in patients with significant bacteriuria did not differ from those of the rest of the patients. This 'abnormality' con firms our opinion that we must consider the increased positive urinary 'abnormalities' in the very old either as a normal phenomenon connected with ageing [1,10] or as a reflec tion of other disease processes present [4,8]. Significant bacteriuria should be treated with drugs only when the aged patient has symp toms of UTI.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients of the 500 ultimately may have benefited from eradication of asymptomatic bacteriuria (although eradication of asymptomatic bacteriuria has not been shown to improve the quality of life, or extend life). [16][17][18][19] Studies show that history and physical examination are the best measures for screening for disease. Delahunt and Turnbull 2~ evaluated patients who were assessed preoperatively for varicose vein stripping or inguinal hemiorrhaphy.…”
Section: Routine Laborawry Testing Is Not the Most Effective Way Of Ementioning
confidence: 99%
“…On the contrary, they may have side-eÂects and can select for antibioticAlthough two studies initially showed a decreased survival in bacteriuric compared with non-bacteriuric resistant strains. Overall, only three presentations (4%) in the present patients [16,17] several more recent studies showed no increase in mortality in this patient group [18][19][20][21]. study were managed ideally, considering the three avenues of management.…”
Section: Resultsmentioning
confidence: 82%